THE EFFECT OF LEARNING WITH ABDUCTIVE-DEDUCTIVE STRATEGY ON HIGH SCHOOL STUDENTS’ REASONING ABILITY - Shodikin, Ali (International Journal of Education, 2017)
The purpose of this research is to investigate the effect of learning with abductive-deductive strategy on the achievement of mathematical reasoning abilities of high school students. It employed the experimental pretest-posttest with non-randomized control group design to the eleventh grade students of one high school in Pati, Central Java, Indonesia. Data were collected in the form of early mathematical ability categories (EMA) and overall. The results showed that the achievement of mathematical reasoning abilities that students acquire through learning with abductive-deductive strategy was better than that of the students who received were taught with expository learning. In more detail, only students in the medium category of EMA showed better achievement in mathematical reasoning abilities. Meanwhile, students of the upper and lower categories had the same achievements in their reasoning abilities. Based on the findings of the research, it is expected that teachers can encourage students to apply abduction and deduction strategy in order to achieve in mathematical reasoning abilities.